2016
DOI: 10.1089/jmf.2015.3513
|View full text |Cite
|
Sign up to set email alerts
|

In VitroandIn VivoImmunomodulatory Activity of Okra (Abelmoschus esculentus L.) Polysaccharides

Abstract: Crude okra (Abelmoschus esculentus L.) polysaccharide (RPS) was obtained by water extraction and alcohol precipitation. Three purified fractions of RPS, designated RPS-1, RPS-2, and RPS-3, were fractioned by diethylaminoethyl (DEAE)-cellulose chromatography. Their molecular weights, monosaccharide compositions, infrared (Fourier transform infrared [FT-IR]) spectra, and nuclear magnetic resonance (NMR) spectra were analyzed. Their immunomodulatory activity was evaluated with an in vitro cell model (RAW264.7 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 41 publications
1
47
0
Order By: Relevance
“…Similar with study conducted by Zha et al (2014), Dendrobium huoshananse polysaccharides at doses of 50, 100, and 200 mg/kg BW increased splenocyte proliferation of 140%, 165%, and 196% respectively. Chen et al (2016) also revealed that administration of okra polysaccharides at doses of 25, 50, and 100 mg/kg BW significantly increase splenocyte proliferation induced by LPS and okra polysaccharide at dose of 100 mg/kg BW showed highest rising of splenocyte proliferation. We can state that higher doses of polysaccharides help in rising the proliferation of B-lymphocytes.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…Similar with study conducted by Zha et al (2014), Dendrobium huoshananse polysaccharides at doses of 50, 100, and 200 mg/kg BW increased splenocyte proliferation of 140%, 165%, and 196% respectively. Chen et al (2016) also revealed that administration of okra polysaccharides at doses of 25, 50, and 100 mg/kg BW significantly increase splenocyte proliferation induced by LPS and okra polysaccharide at dose of 100 mg/kg BW showed highest rising of splenocyte proliferation. We can state that higher doses of polysaccharides help in rising the proliferation of B-lymphocytes.…”
Section: Resultsmentioning
confidence: 75%
“…Similarly, study conducted by Chen et al (2016) showed that highest dose of okra polysaccharides (100 mg/kg BW) increased the spleen index significantly with cyclophosphamide as an antigen. Our present result suggested that okra polysaccharides enhance spleen weight and induce the increase in number of splenocytes in spleen.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations